The study different forms of common bean to anthracnose resistance using seedlings and DNA markers - Anokhina, Vera S.; Xiao, Yutin; Karpievich, Vadim A.; Sauk, Irina B.; Romanchuk, Irina Yu. (Experimental Biology and Biotechnology, 2019)
The results of study of various forms of common bean (Phaseolus vulgaris L.) to anthracnose resistance using seedlings and molecular testing for the Co-14 and Phg-1 genes were presented. The different responses of the samples to the influence of the pathogen were revealed. The lines from mutant forms that had the Co-14 and Phg-1 genes in their genomes were selected.
Keywords: anthracnose; genotype; seedling; DNA marker; common bean